Research as development biomedical research, ethics, and collaboration in Sri Lanka - Sariola, Salla; Simpson, Bob 1956- (Cornell University Press, 2019)
"Shows how international biomedical researchers in Sri Lanka work across cultural, epistemic, economic, and power differences to accomplish clinical trials"...